Effects of carbon and nitrogen sources on the antibacterial activity of Bacillus tequilensis BSM-F symbiotic with Halichondria panicea sponge from the Cabbiya Coast, Madura, Indonesia - Achmad Toto Poernomo; Sonia Khoirun Nisa; Zahratus Silmi Aliyah; Isnaeni Isnaeni (Pharmaciana, 2020)
Sponges form obligate symbiotic associations with antibiotic-producing microorganisms. Many factors, including climate change, anthropogenic pollution, introduced species, and nutrient enrichment, have all been linked to the specific character of marine-symbiotic microorganisms. This recent study investigated the effects of carbon and nitrogen sources on the antibacterial activity of Bacillus tequilensis BSM-F in solid fermentation media, Zobell Marine Agar (ZMA), ZMA was added with various carbon and nitrogen sources at different concentrations to evaluate the effect of enrichment media on the antibacterial activity. The carbon sources used were glucose, glycerol, lactose, and starch, while the nitrogen sources were beef extract, soybean meal, malt extract, and casein. Each of which was added to ZMA at 0.5%, 1%, 1.5%, and 2% w/v. The inhibitory activity was denoted as the activity index, i.e., the ratio of the diameter of zone of inhibition to the diameter of the bacterial colony. B. tequilensis BSM-F exhibited the highest inhibitory activity against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922 when cultured in media containing glycerol and casein. The optimum condition was achieved when glycerol and casein were each added to ZMA at 1.5% w/v.